Brucella Non-Neutrocytic Bacterascites in a Patient with Chronic Liver Disease - Bruno Marmelo; Telma Pereiro; Paula Sousa; Joana Capelo; Adelino Carragoso (European Journal of Case Reports in Internal Medicine, 2015)
Objectives: To report a case of Brucella peritonitis. Patient and methods: We describe the case of a patient and present a brief review of the few published reports. Results: The patient had alcoholic cirrhosis of the liver and was diagnosed with Brucella non-neutrocytic bacterascites. Conclusion: Brucellosis is a common zoonosis with worldwide distribution. It is a systemic disease with the potential to predominantly affect one organ or a specific system (focal brucellosis). However, peritoneal focalization of this disease is a very rare presentation.